Subliminal activation of abandonment- and eating-related schemata: relationship with eating disordered attitudes in a nonclinical population - Meyer, Caroline; Waller, Glenn (The International journal of eating disorders, 2000)
Objective Previous research has demonstrated that subliminal abandonment cues can facilitate eating behavior. It is believed that such eating is a response to the activation of specific core schemata. However, the precise nature of those schemata has not been established. This study examined whether the presentation of subliminal abandonment and food/shape cues results in the activation of abandonment‐related or food‐related schemata. Method Eighty‐two women were exposed to one of three subliminal cues— an abandonment cue (“lonely”), an appetitive cue (“hungry”), and a neutral cue (“gallery”). They subsequently completed Stroop tasks to measure activation of relevant schemata. Results Subliminal presentation of abandonment cues led to the activation of food‐ and shape‐related schemata. In contrast, subliminal appetitive cues resulted in an activation of abandonment‐related schemata. Conclusions The results show preliminary support for a multilevel cognitive model, involving indirect links between subliminal cue type and the activation of eating‐related cognitions. © 2000 by John Wiley & Sons, Inc. Int J Eat Disord 27: 328–334, 2000.